Anganwadi centres in society - George, Neethu; Selvaraju, Mani Prabhu; Elavarasu, Swathi; Ravichandran, Tharun (International Journal Of Community Medicine And Public Health, 2021)
According to Mahatma Gandhi, “if you educate a man you educate an individual, but if you educate a woman you educate an entire nation.” India, in spite of having the world’s largest youth population, it has been struggling a lot with the lack of efficient implementation of various policies in the health care system. Since majority of India’s population is still residing in the villages, which have a greater say in the overall development of the nation but they are left untouched most of the times either due to improper implementation of the policies or hindrances in the process of development of health care system. Anganwadi’s are India’s backbone in delivering the healthcare that everyone in country can access to it, by focussing on nutritional supplementation, women’s health and so on. This paper is an attempt to shine the light on the impact of the Anganwadi centres in improving the health status of people in the rural areas at grassroot level, focusing especially on women and children’s health and the association between the potential contribution of the Anganwadi workers and the child health indicators. Also, current pandemic influences on the centres were quoted.